Synthesis of ABA-type double hydrophilic amphiphilic PU-based block copolymers of poly(N-Vinylpyrrolidone) and poly(N-isopropylacrylamide) via click chemistry - Vishwakarma N.K.; Patel V.K.; Mitra P.; Ramesh K.; Mitra K.; Vishwakarma S.; Acharya K.; Misra N.; Maiti P.; Ray B. (My University, 2025)
Double hydrophilic ABA-type amphiphilic polyurethane (PU)-based poly(N-vinylpyrrolidone) (PNVP)-b-PU-b-PNVP and poly(N-isopropylacrylamide) (PNIPAM)-b-PU-b-PNIPAM triblock copolymers have successfully been synthesized via the combination of the step-growth polymerization, reversible addition-fragmentation chain transfer (RAFT) polymerization and azide-alkyne click reaction. All polymers are characterized by 1H NMR, FTIR, and gel permeation chromatography. The cmcs of PNVP-b-PU-b-PNVP block copolymers increase with increase in PNVP block length: 0.0019 mg/mL for PNVP39-b-PU-b-PNVP39 and 0.005 mg/mL for PNVP68-b-PU-b-PNVP68. The iron-chelating ability and the reducing power of PNVP68-b-PU-b-PNVP68 are superior to that of PNVP owing to the presence of urethane moiety of PU block in copolymer. The LCST of PNIPAM-b-PU-b-PNIPAM are lower than that of PNIPAM (33 °C): 23.5 and 25.5 °C for PNIPAM42-b-PU-b-PNIPAM42 and PNIPAM66-b-PU-b-PNIPAM66, respectively. © 2020 Taylor & Francis Group, LLC.